Electric-field control of the remanent-magnetic-state relaxation in a piezoelectric-ferromagnetic PZT-5%Fe3O4 composite - Vertsioti, G.; Pissas, M.; Zhang, S.J.; Stamopoulos, D. (JOURNAL OF APPLIED PHYSICS, 2019)
Magnetoelectric (ME) composites that exhibit both ferroelectric and ferromagnetic properties have attracted significant attention, thanks to their potential applications, e.g., low-energy-consumption storage devices. Here, we study bulk composites based on Pb(Zr0.52Ti0.48)O-3 (PZT) as a piezoelectric (PE) matrix and Fe3O4 nanoparticles (NPs) as soft ferromagnetic (FM) and magnetostrictive additives, in the form PZT-xFe(3)O(4) with 0%<= x <= 50wt.%, all sintered at T=1000 degrees C for 2h in air. We focus our study on a completely insulating sample x=5% and measure its properties at room temperature upon an out-of-plane external electric field, E-ex: namely, piezoelectric response [in-plane strain, S(E-ex)], polarization [P(E-ex)], and relaxation of the remanent magnetization, [m(rem)(t,E-ex)], prepared upon application and removal of an external magnetic field. The peaks observed in the butterflylike S(E-ex) curves at E-peak(+/-)=+/- 6kV/cm and the nucleation field recorded in the P(E-ex) loops at the same range around E-nuc(+/-)=+/- 6kV/cm (both referring to the PZT PE matrix) are clearly imprinted on the relaxation behavior of the m(rem)(t,E-ex) data (referring to the Fe3O4 FM NPs). This experimental fact proves the ME coupling between the PZT matrix and the embedded Fe3O4 NPs. We ascribe this feature to the comparable piezoelectricity of the PZT matrix and the magnetostriction of the Fe3O4 NPs that probably motivate and/or promote a strain transfer mechanism occurring at the PZT matrix-Fe3O4 NP interfaces. Our work proves that the low cost PZT-xFe(3)O(4) composite is a promising candidate ME material for future studies, aiming to potential applications.